The Mode of Action of Thrombin - Laki, K; Gladner, Jules A.; Folk, J. E; Kominz, D. R (Thrombosis and Haemostasis, 1958)
The peptides liberated from fibrinogen by the action of thrombin have been isolated on modified cellulose adsorbents. These peptides have been characterized by sedimentation-diffusion measurements by quantitative amino acid analysis, and by C-terminal analysis. Both peptides were found to contain arginine as C-terminal amino acid. Thrombin thus splits specific arginyl-glycine bonds in the fibrinogen molecule. The specificity of thrombin is discussed in view of the finding that the active center of thrombin is similar to that of trypsin and chymotrypsin.